Litter Windrows in the South-East Coast of the Bay of Biscay: An Ocean Process Enabling Effective Active Fishing for Litter - Ruiz, Irene; Basurko, Oihane C.; Rubio, Anna; Delpey, Matthias; Granado, Igor; Declerck, Amandine; Mader, Julien; Cózar, Andrés (Frontiers in Marine Science, 2020)
Large scale convergence regions of floating marine litter are commonly observed in semi-enclosed seas as the Bay of Biscay. However, clean-up activities on such accumulation regions are limited by the spread of the large-size floating litter on the sea surface. Data gathered by a small-scale fishing vessel devoted to active fishing for floating litter activities during the spring and summer of 2018 reveals that the linear streaks of high concentration of floating litter (so-called litter “windrows”) are common accumulation structures in the south-east coast of the Bay of Biscay. The random search of litter windrows for their collection through surface tows of macro-nets was proved to be an effective action for floating litter mitigation. A total of 196 tows collected 16.2 tons of floating marine litter in 68 working days. Most of the litter windrows were around 1 km length and, on average, accumulated 77.75 kg of floating marine litter. Fishing, shipping and aquaculture sectors were the source of 35% of the 4,130 litter items analyzed (55% in weight of the sourced items), and plastic was the most common type of material (96% in terms of items). A better understanding of the phenomenon of the litter windrows, capable to guide clean-up efforts in space and time, would provide a considerable improvement in the efficiency of mitigation actions to reduce the marine litter pollution. The observations of litter windrows in the coastal area of the south-east of the Bay of Biscay demonstrate the key role of submesoscale processes in the distribution of FML. The present work provides a thorough description of floating litter windrows in nature, which it was non-existent to date. The results are the kind of proof necessary to boost the research addressed on the submesoscale aggregations of FML. Coupling litter windrows observations with remote-sensing technology and high-resolution modeling techniques offer great opportunities for the mitigation actions against marine litter.